Organisational Principles in European Administration: Focusing on Foreign Policy Organs and the Administrative Procedure of Consular Protection in Third Countries - Csatlós, Erzsébet (Decentralizacja i centralizacja administracji publicznej. Współczesny wymiar w teorii i praktyce, 2019)
“Supported by the UNKP-17-4 New National Excellence Program of the Ministryof Human Capacities”.